Criticism of the Language of the Common People in Al-Misbāh Al-Munīr by Al-Fayoumi (770 AH) - Al-Essa, Maha Abdulaziz (Journal of Arabic Language Sciences and Literature, 2023)
This research aims to identify the Fayyoumi approach in criticizing the language of the common people, as well as the criteria on which his criticism was based, by analyzing models of the criticism of the language of the common people contained in his book (Al-Misbāh Al-Munīr fiī Gharīb al-Sharh al-Kabīr). Furthermore, it aims to verify the validity of those criticisms by placing them on the scale of language, and standing on Scholars' opinions about it; To arrive at the judgment of whether his criticism is valid or not.In order to achieve the aims of this research, the researcher relied on the inductive-analytical approach. It consists of an introduction, a preface, two chapters, and a conclusion. In the introduction, I highlighted the significance of research, its questions, aims, methods, and past studies, and the research plan. The first section focused on the study of sound criticism, while the second section was focused on the study of semantic criticism. Then came the conclusion, in which I presented the most important findings of the research, which included: Al-Fayoumi used to mention the correct or correct language (al-Lughah al-faah) first, then he referred to the language of the common people (usually the incorrect one), and this is one of the most prominent features of his approach in criticizing the language of the common people. The conclusion also includes that Al-Fayoumi based his critique of common people's language in certain areas on precise scientific criteria, such as poetry, and what has been passed down through generations from imams of Arabic language, along with other research results and recommendations, which I included in the study's conclusion.*This article is taken from research submitted to obtain a master’s degree in linguistics, entitled: “Linguistic Criticism in Al-Misbah Al-Munir by Al-Fayumi”. Presented by: Maha Abdul Aziz Al-Issa, under the supervision of Dr.Muqbil Ali Al-Adadi Al-Hudhali.
Keywords: linguistic criticism; jurisprudential (Fiqhī) lexicon; linguistic lexicon; Arabic dictionaries